ANALISIS POLA SESAR DI PULAU SULAWESI BERDASARKAN DATA GEMPA BULAN FEBRUARI TAHUN 2022 DI BBMKG WILAYAH IV MAKASSAR - Andira, A. Andira Maharani; Minarti (SAINFIS: Jurnal Sains Fisika, 2022)
Has been research in  the Office of the Meteorology, Climatology and Geophysics Center (BBMKG) Region IV Makassar, precisely in the earthquake and tsunami early warning room on February 2022. The purpose of this Field Work Practice activity is to find out Regional Earthquake Center (PGR) IV Makassar operational system and to analyze and process earthquake parameter data to an advanced level from the results of SeisComp3 analysis. Based on the map, the most earthquakes occur in the Matano fault. The Matano Fault is an extension of the Palu-Koro fault from the northwest to the southeast that intersects Lake Matano. The largest accumulation of energy is in the Matano fault which indicates that the fault is active and has the potential to produce a large earthquake. The results of this activity are 2. The average earthquake in February 2022 recorded in the PGR IV area is a maximum of 28 earthquake events and a minimum of 2 events with a total of 261 earthquake events. Dominated by earthquakes with a magnitude of 2 to 3 SR and generally shallow depths.